Spectrum of the Microorganisms in Children with Urinary Tract Infection - Saba Afzal, Samiya Naemullah; Saba Afzal, Samiya Naemullah (Journal of Rawalpindi Medical College, 2008)
Background: To determine the spectrum of microorganisms and their sensitivities in children with urinary tract infection (UTI.) Methods: This study was conducted in Pediatrics department of Holy Family Hospital, Rawalpindi. 150 children between 1 – 12 years of age presenting with fever ≥ 101 °F with duration of 10 days or less without any definite focus of infection were included in the study. Children who already had received antibiotics in previous 48 hours or were comatose, immunocompromised or with congenital urinary tract abnormalities were excluded from the study. Results: Escherichia. coli and Klebsiella were the commonest uropathogens. Other uropathogens obtained were Proteus mirabilis, Enterobacter and Staphylococcus aureus. Maximum sensitivity was to co-amoxiclav, cephalosporins aminoglycosides and quinolones. Organisms showed maximum resistance to ampicillin, amoxicillin and nalidixic acid with low resistance to cephalosporins, quinolones and aminoglycosides. Conclusion: UTI is a common source of infection among children presenting with unexplained fever. Co-amoxiclav or cephalosporins can be started as an empirical agent that can be changed later according to the culture and sensitivity report.